A comparison of the mental toughness of players in team and individual sport during periodization - Janse van Rensburg, Chrisna (University of the Free State, 2015)
The contribution of psychological skills on performance enhancement and mental toughness attributes and development is still limited within the sport context, even though it has numerously been proven to be an important factor that influences the success of sport achievement outcomes. No concise agreement towards the prescription of the development and improvement of mental toughness has been designed in order to improve the athletes’ mental toughness during their annual training programs. The aim of this dissertation was to explore the differences in mental toughness of rugby players during periodization phases, as well as the differences between the rugby forwards’ and backs’ mental toughness. The differences between the mental toughness of golf players and rugby players have also been explored during periodization phases. Data from rugby players and golf players, who participate in sport on a university and regional level, had been obtained by means of the Psychological Performance Inventory that was completed by all players during the preparatory, competition, and transition periodization phases. Differences in mental toughness of rugby players between preparatory, competition and transition periodization phases were analysed using a repeated measures mixed linear model with periodization phase, team and group (forwards versus backs) as fixed effects, and fitting an unstructured covariance matrix to the repeated measures of mental toughness. From this model, mean values for each group and phase, as well as differences between mean values between periodization phases together with associated p-values and 95% confidence intervals were calculated. The data on mental toughness were compared between rugby players and golf players through a one-way analysis of variance with group (rugby vs golf) as factor, allowing for different residual variances for the two groups. The results indicated that significant differences had been found amongst rugby players with regards to their attitude control (p=0.00) that revealed significantly higher values during competition phase than during the preparation phase. When the components of mental toughness had been compared for the competition phase and the transition phase, significant differences were found for overall mental toughness (p=0.01), motivation (p=0.04), and attitude control (p=0.05), with the latter phase having scored lower than the competition phase. No significant differences were found between the mental toughness components of the preparation phase compared to the transition phase. The mental toughness of forwards and backs revealed no significant differences, although a tendency occurred where the backs obtained higher mean values for all of the mental toughness components. Significant differences had only been found for negative energy control between the golf players and rugby players. Negative energy control differed significantly (p=0.03) where the golf players portrayed much better values during the transition periodization phase than the rugby players’ negative energy control values. This is the first study designed to explore mental toughness of rugby players and golf players during periodization phases, and could be the foundation for future studies to the further investigate which mental toughness components seems to be dominant during specific periodization phases – and which components still have room for improvement, while comparing the physical performances and parameters of the athletes as well – in order to facilitate with the development of training guidelines that enhances athletes’ performances and help them to achieve their goals.

Die bydrae van psigologiese vaardighede op die verbetering van prestasie, asook die ontwikkeling van psigiese gehardheid is steeds beperk binne die sport konteks, alhoewel dit met talle geleenthede bewys is as `n belangrike faktor wat die sukses van sport-uitkomste beïnvloed. Geen bondige ooreenstemmings teenoor die voorskrifte van die ontwikkeling en verbetering van psigiese gehardheid is al ondersoek om sportlui se psigiese gehardheid tydens hul jaarlikse oefenprogramme te verbeter nie. Die doel van hierdie verhandeling was om die verskille tussen rugby spelers se areas van psigiese gehardheid tydens verskillende periodiseringsfases, asook die verskille tussen rugby voor-en agterspelers se psigiese gehardheid, te ondersoek. Die psigiese gehardheidsverskille tussen golf en rugby is ook tydens die periodiseringsfases ondersoek. Data is vanaf rugby en golf spelers, wat op universiteits- en streeksvlakke deelneem, deur middel van die Psigologiese Vaardighede Inventaris verkry, wat deur al die spelers tydens voorbereidende fase, kompetisie fase en oorskakelingsfase voltooi is. Die psigiese gehardheidsverskille van die rugby spelers tydens die periodiseringsfases is ontleed deur `n herhalende-metode-gemengde-liniêre-model waar periodiseringsfase, span en groep (voorspelers teenoor agterspelers) as vasgestelde effekte gebruik is en `n ongestruktureerde kovariansiematriks tot die herhalende metodes van psigiese gehardheid ingestel is. Vanuit hierdie model is gemiddelde waardes vir elke groep en fase, sowel as die verskille tussen die gemiddelde waardes tussen die periodiseringsfases saam met die geassosieerde p-waardes en 95% intervalle bereken. Die data vir die psigiese gehardheid tussen rugby spelers en golf spelers was vergelyk deur middel van `n eenrigting-variansie analise met groep (rugby teenoor golf) as faktor, wat verskillende oorblywende afwykings vir die twee groepe meegebring het. Die resultate het aangedui dat betekenisvolle verskille tussen rugby spelers gevind is met betrekking tot die komponent houding (p=0.00) wat hoër waardes tydens die kompetisie fase in vergelyking met die voorbereidingsfase getoon het. Toe die komponente van psigiese gehardheid tussen die kompetisie fase en oorskakelingsfase vergelyk is, is betekenisvolle verskille gevind vir algehele psigiese gehardheid (p=0.01), motivering (p=0.04) en houding (p=0.05), waar die oorskakelingsfase laer waardes as die kompetisie fase behaal het. Geen betekenisvolle verskille is gevind vir die komponente van psigiese gehardheid tussen die voorbereidingsfase en die oorskakelingsfase nie. Die psigiese gehardheid van die voor-en agterspelers het geen betekenisvolle verskille getoon nie, alhoewel `n tendens waargeneem is waar die agterspelers hoër gemiddelde waardes vir al die komponente van psigiese gehardheid behaal is as die voorspelers. Betekenisvolle verskille is slegs gevind vir negatiewe energie beheer tussen golf spelers en rugby spelers. Negatiewe energie beheer het betekenisvol verskil (p=0.03) waar die golf spelers baie beter waardes getoon het tydens die oorskakelingsperiodiseringsfase as die rugby spelers se negatiewe energie beheer waardes. Hierdie is die eerste studie wat uitgevoer is om psigologiese gehardheid van rugby spelers en golf spelers tydens verskillende periodiseringsfases te ondersoek en kan die fondasie vir toekomstige studies wees. Verdere ondersoek kan ingestel word rakende watter psigologiese gehardheid-komonente dominant tydens spesifieke periodiseringsfases voorkom, asook watter verbeter kan word – terwyl die fisieke prestasies en parameters van sportlui daarmee vergelyk word – om sodoende die ontwikkeling van oefeningsriglyne te fassiliteer wat sportlui se prestasie kan verbeter en hul help om doelwitte te kan bereik.
Dissertation (M.A. (Exercise and Sport Science))--University of the Free State, 2015
Keywords: Mental toughness; Rugby; Golf; Periodization phases; Periodization training; Athletes -- Mental health; Rugby football players --Psychological aspects; Golf -- Psychological aspects